End of the third world : newly industrializing countries and the decline of an ideology - Harris, Nigel (I.B. Tauris LondonGB, 1986)
Discusses theories that gave rise to the concept of the third world especially those relating to development economics. Tests these theories against the development of four Asian and two Latin American countries. Determines the peculiarities of these countries by comparing them with other less developed countries and their manufacturing industries with those of the more developed countries. Summarizes the implications for third worldism. Examines role of the state and of governments in the pattern of rapid growth. Discusses social interests embodied in the ideology of third worldism.